2001
DOI: 10.1002/cncr.9047
|View full text |Cite
|
Sign up to set email alerts
|

Fine-needle aspiration cytology of adrenal masses in noncancer patients

Abstract: Designing an active site: A new type of core–shell structured catalyst was prepared, with a uniform SiO2 core supporting Pd nanoparticles (NPs) covered with a Ti‐containing mesoporous silica shell. Generated H2O2 on the inner Pd NP site could interact with the Ti oxide moieties within the mesopores before dispersion to the solvent can occur, which ultimately enhances the oxidation activity for one‐pot oxidation of sulfide to sulfoxide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(19 citation statements)
references
References 33 publications
0
18
0
1
Order By: Relevance
“…Inclusion criteria and definition of reference standard differed from the imaging meta-analysis mainly in population selection criteria (as adrenal biopsy is not indicated in incidentaloma population but rather in patients at high risk for malignancy) and in reference standard (where we accepted imaging and clinical follow-up in addition to histopathology, as most metastases would not undergo adrenalectomy). We identified 32 studies (90,113,114,115,116,117,118,119,120,121,122,123,124,125,126,127,128,129,130,131,132,133,134,135,136,137,138,139,140) with a total of 2174 patients which reported at least one outcome of interest (complication rate, nondiagnostic rate, diagnostic accuracy parameters). Of these, only 8 studies (90,126,127,130,131,132,133,140) were included for the diagnostic accuracy analysis, reasons for exclusion being lack of any or optimal reference standard for at least 50% patients (n = 20) and more than 30% patients with nonadenomas in benign cohort (n = 4).…”
Section: Value Of An Adrenal Biopsy (Question 1b)mentioning
confidence: 99%
“…Inclusion criteria and definition of reference standard differed from the imaging meta-analysis mainly in population selection criteria (as adrenal biopsy is not indicated in incidentaloma population but rather in patients at high risk for malignancy) and in reference standard (where we accepted imaging and clinical follow-up in addition to histopathology, as most metastases would not undergo adrenalectomy). We identified 32 studies (90,113,114,115,116,117,118,119,120,121,122,123,124,125,126,127,128,129,130,131,132,133,134,135,136,137,138,139,140) with a total of 2174 patients which reported at least one outcome of interest (complication rate, nondiagnostic rate, diagnostic accuracy parameters). Of these, only 8 studies (90,126,127,130,131,132,133,140) were included for the diagnostic accuracy analysis, reasons for exclusion being lack of any or optimal reference standard for at least 50% patients (n = 20) and more than 30% patients with nonadenomas in benign cohort (n = 4).…”
Section: Value Of An Adrenal Biopsy (Question 1b)mentioning
confidence: 99%
“…Lumachi et al [52] reported the results of FNA biopsy (21-23 gauge) in 70 patients with functioning (n=38 patients) and non-functioning (n=32 patients) adrenal masses (median size, 4 cm; range, 3-12 cm). The smear adequacy rate was 95%; definitive histology was available for 97% of patients, including ten patients with ACC.…”
Section: Mri and The Indeterminate Adrenal Massmentioning
confidence: 98%
“…The summary characteristics of the included studies are presented in Table 1 (13,25,26,28,30,32,41), suggesting a highly selected population (Table 1). Information on a total of 2190 adrenal biopsies (13-277 per study) was reported in 32 studies ( Table 2).…”
Section: Included Studiesmentioning
confidence: 99%
“…Of the 175 studies, 95 were excluded based on abstract screening and the remaining 80 full-text papers were reviewed. Of these, 32 studies (7,8,9,10,13,16,17,19,21,22,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42) reported at least one outcome of interest and were included. Studies were primarily excluded due to no outcome of interest (n = 19), <10 patients (n = 12), abstract only without subsequent full paper publication (n = 8), patient overlap (n = 7), ex vivo biopsy (n = 1), and case-control study (n = 1).…”
Section: Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation